دور تكنولوجيا المعلومات في تحسين الممارسات المحاسبية بالجزائر. - بن زاف, لبنى (جامعة الوادي University of Eloued, 2020)
يهدف هذا البحث لابراز دور تكنولوجيا المعلومات في تحسين الممارسات المحاسبية بالجزائر حيث اصبح لزاما على المؤسسات عصرنة وتطوير انظمتها المعلوماتية بما فيها النظام المحاسبي للحصول على معلومات ذات جودة تترجم على شكل تقارير مالية تساعد مستخدميها في اتخاذ القرار الامثل. خلصت الدراسة الى مجموعة من النتائج اهمها ان استخدام تكنولوجيا المعلومات سهلت الممارسة المحاسبية وساعدت على تقديم معلومات دقيقة تدعم عملية اتخاذ القرار في الوقت المناسب وتحسين الاداء المالي للمؤسسة. This research aims to highlight the role of information technology in improving accounting practices in Algeria, as it has become imperative for institutions to modernize and develop their information systems, including the accounting system, to obtain quality information translated into financial reports that helps its users in making the optimal decision. The study concluded a set of results, the most important of which is the use of information technology that has facilitated accounting practice and helped to provide accurate information that supports decisionmaking in a timely manner and improves the financial performance of the institution.
The role of information technology in improving accounting practices in Algeria
مقال
Keywords: تكنولوجيا المعلومات،نظام المعلومات المحاسبي ،ممارسات المحاسبة،الجزائر.